PERAN KEPERCAYAAN MEMBANGUN LOYALITAS - Khoirunisa Kesuma Dhani (Prodi Magister Manajemen FE-UST, 2019)
The purpose of this study are: (1) To know the influence of service and product quality to the level of trust (2) To know the effect of product and service quality to customer loyalty (3) To know the level of trust influence to customer loyalty. The population in this study are clients of Tax Consultant Office Albertus M Santosa. This research use purposive sampling sampling technique. The sample in this research is the permanent client in Tax Consultant Office Albertus M Santosa for at least 2 years. The formula sampling used the Slovin Formula. Data collection techniques using questionnaires. The analysis used is inferential analysis and path analysis. The research result concluded that : (1) The Service and product quality has a significant positive effect on trust level, (2) The Service and product quality has a positive effect significant to customer loyalty, (3) Trust levels have a positive effect significant to customer loyalty. Keywords : Service quality, Product quality, Level of confidence, Customer loyalty.